Investigating cold Aδ fibers in the 0–40 °C temperature range: A quantitative sensory testing and evoked potentials study - Lithfous, Ségolène; Trocmet, Louise; Pebayle, Thierry; Després, Olivier; Dufour, André (Clinical neurophysiology, 2022)
•Thermal stimuli with decreasing intensity from 40 °C elicit a cool sensation, with a detection threshold of 35 °C.•Thermal stimuli elicit evoked potentials with an N2P2 component whose latency is within the Aδ fiber range and amplitude is positively correlated with cooling amplitude.•Cold temperature discrimination starts to increase below 32 °C, peaks at 20 °C, and then decreases for temperatures below 16 °C. To evaluate the activity of cold Aδ-type fibers to thermal stimuli above human skin temperature (i.e., >32 °C). Twenty young adults aged 20–24 years participated in this study. The cold-detection threshold was measured from a basal temperature of 40 °C using an adaptive staircase method with high-speed cooling ramps (170 °C/s). A total of 150 stimulations at 36 °C, 32 °C, 28 °C, 24 °C, 20 °C, 16 °C, 12 °C, 8 °C, 4 °C and 0 °C (15 each) were performed. After each stimulation, subjects estimated the intensity of cold sensation using a visual analog scale, and evoked potentials were recorded. The average cold-detection threshold was 35 °C (SD = 1.8). Regardless of the stimulation temperature, subjects reported a cooling sensation. Interestingly, reported increments in sensation were prominent for stimulation temperatures between 32 °C and 20 °C, but below this latter temperature sensations varied only very slightly. Evoked potential recordings revealed that decreasing temperature stimuli from a baseline of 40 °C induced a previously unreported N2P2 component with a mean N2 peak latency of 275 ms (SD = 13.1). The peak-to-peak amplitude of the N2P2 complex increased as the intensity of the cooling stimulation increased, exhibiting a profile comparable to subject-perceived intensity, namely, a major increase up to 20 °C, followed by a plateau to 0 °C. The cool sensations reported by subjects were likely conveyed by Aδ fibers rather than by slow-conducting C fibers. Moreover, our rapid stimulation technique starting from a high temperature (40 °C) was capable of a) generating cold sensations at stimulation temperatures between 36 °C and 32 °C, and b) revealing the optimal activation range of Aδ fibers (20 °C–28 °C). Any decrease in temperature below this range did not result in a significant increase in sensation and thus probably did not evoke a significant increase in Aδ fiber activity. The regular assessment of cold sensation in peripheral neuropathies (i.e., with temperatures below 32 °C), could be completed by investigating cold-detection thresholds at temperatures ranging from 40 °C to 32 °C. Indeed, the absolute threshold of cold perception appears to start at 35 °C. Changes in the activation threshold of cold fibers were more easily detectable at this level.